Polyarteritis Nodosa: an unusual case of paraneoplastic process in renal cell carcinoma - Umair Ahmed; Tulika Chatterjee; Manasa Kandula (Greater Baltimore Medical Center, 2020)
Polyarteritis Nodosa (PAN) is a small and medium vessel necrotizing vasculitis that can affect any system in the human body. Rarely, PAN can be the primary manifestation of an underlying malignancy. The association between malignancy and vasculitis is an ongoing topic of research. Our patient's presentation suggests malignancy may be a trigger for acute onset vasculitis and therefore once a malignancy is identified, therapy should be targeted towards treating the malignancy rather than the vasculitis alone.